Porous PVdF-HFP/P123 electrolyte membrane containing flexible quasi-solid-state dye-sensitized solar cells produced by the compression method - Kim, Jae Hong; Jung, Hee Suk; Park, Chung Hee; Kang, Tae Jin (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Flexible quasi-solid-state dye-sensitized solar cells (DSSCs) with porous poly(vinylidenefluoride-co-hexafluoropropylene) (PVdF-HFP)/polyethylene oxide-co-polypropylene oxide-co-polyethylene oxide (P123) electrolyte membranes were fabricated and their photocurrent-voltage (I-V) characteristics are studied. Flexible TiO2 photoelectrodes were prepared using the compression method and porous PVdF-HFP/P123 membranes, by the nonsolvent-induced phase inversion technique. To activate the electrolyte membrane, the membrane was immersed in liquid-state electrolyte. Increased compression pressure improved the interconnection between TiO2 nanoparticles, enhancing the photovoltaic performances of the flexible liquid-state DSSCs to a maximum of 3.92% efficiency. Meanwhile, the overall pore structure of the PVdF-HFP/P123 membranes was controlled by varying the blend ratio of P123 to PVdF-HFP. Membranes higher in P123 content gave larger pores and pore volume, increasing the electrolyte uptake of the porous membrane, and thus the ionic conductivity of the electrolyte membrane as well. The photovoltaic characteristics of the flexible quasi-solid-state DSSCs containing a porous PVdF-HFP/P123 electrolyte membrane showed a maximum at 50 wt% P123 content, which gave a short-circuit current density (J(sc)) value of 7.28 mA/cm(2), an open-circuit voltage (V-oc) of 0.67 V, a fill factor (FF) of 0.61 and an energy conversion efficiency (eta) of 2.98%. Furthermore, the device designed in this study showed good durability compared to those based on liquid-state electrolyte. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: LOW-TEMPERATURE FABRICATION; RENEWABLE ENERGY; TIO2 FILM; NANOPARTICLES